اتجاهات الشباب الجامعي نحو ممارسة العمل الحر: دراسة مطبقة على طلاب كلية الاقتصاد والعلوم الإدارية بجامعة الإمام محمد بن سعود الإسلامية - الزير، سعد بن راشد بن عبدالله (جامعة الإمام محمد بن سعود الاسلامية - عمادة البحث العلمي, 2021)
استهدفت الدراسة التعرف على مستوى اتجاهات الشباب الجامعي نحو ممارسة العمل الحر، وذلك من خلال جوانب ثلاثة: الجانب المعرفي والوجداني والسلوكي. كما هدفت الدراسة إلى التعرف على دور الجامعة في تنمية وتعزيز اتجاهات الطلاب نحو العمل الحر. وتنتمي هذه الدراسة إلى نمط الدراسات الوصفية معتمدة على منهج المسح الاجتماعي لمناسبته لهذا النوع من الدراسة. وقد طبقت الدراسة على طلاب كلية الاقتصاد والعلوم الإدارية الذكور المنتظمين للعام الدراسي (1441هـ) في مرحلة البكالوريوس. وقد أجريت الدراسة على عينة تعمديه بلغت (205) طالبا باستخدام أداة واحدة تمثلت في الاستبانة. وقد توصلت الدراسة إلى نتائج متعددة أبرزها: وجود اتجاه إيجابي مرتفع جدا في الجانب الوجداني ومرتفع في الجانب السلوكي ومتوسط في الجانب المعرفي. أما دور الجامعة في تنمية اتجاهات الطلاب نحو العمل الحر فقد حقق مستوى منخفضا في ذلك، كما أظهرت النتائج عدم وجود علاقة ذات دلالة إحصائية بين اتجاه الطلاب نحو العمل الحر والتخصص الدراسي، مستوى تعليم الوالدين، عمل الوالد، والمعدل التراكمي للطالب، في حين أثبتت الدراسة وجود علاقة ذات دلالة إحصائية بين اتجاهات الطلاب نحو العمل الحر ومستوى دخل الأسرة.
The study aimed to identify the level of attitudes of university students towards self-employment through cognitive, emotional, and behavioral aspects. The study also aimed to identify the university's role in developing and enhancing their attitudes towards self-employment. This study belongs to the pattern of analytical descriptive studies where the social survey method was used. The study was applied to all male students enrolled at the College of Economics and Administrative Sciences, who are bachelor's degree students attending the academic year (1441 AH). The study was conducted on a deliberate sample of (205) students using one tool, which was the questionnaire. The study reached several results, most notably: the presence of a very high positive attitude in the emotional and behavioral aspects, but medium in the cognitive aspect. As for the university’s role in developing the students’ attitudes towards self employment, it has achieved a low level, and the results showed that there is no statistically significant relationship between the students’ attitude towards self-employment and academic specialization, the level of parents’ education, the father’s work, and the student’s GPA. However, the study demonstrated that there is a statistically significant relationship between the students' attitudes towards self-employment and the level of family income.
Keywords: المؤسسات الجامعية -- التنمية الطلابية -- التخصص الدراسي -- العمل الحر -- طلبة الجامعات